2017
DOI: 10.1371/journal.pgen.1006657
|View full text |Cite
|
Sign up to set email alerts
|

Novel genes involved in severe early-onset obesity revealed by rare copy number and sequence variants

Abstract: Obesity is a multifactorial disorder with high heritability (50-75%), which is probably higher in early-onset and severe cases. Although rare monogenic forms and several genes and regions of susceptibility, including copy number variants (CNVs), have been described, the genetic causes underlying the disease still remain largely unknown. We searched for rare CNVs (>100kb in size, altering genes and present in <1/2000 population controls) in 157 Spanish children with non-syndromic early-onset obesity (EOO: body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 60 publications
3
28
0
1
Order By: Relevance
“…Glessner et al (2010) found a lack of contribution for common CNVs, including the FTO gene, and proposed CNVs that are exclusive to both European and African ethnicities. None of the studies, including rare CNV in the etiology of severe earlyonset obesity or novel CNV associated with familial obesity, have found CNV of FTO relevant, which supports a lack of CNV contribution to genetic risk for obesity (Serra-Juhé et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…Glessner et al (2010) found a lack of contribution for common CNVs, including the FTO gene, and proposed CNVs that are exclusive to both European and African ethnicities. None of the studies, including rare CNV in the etiology of severe earlyonset obesity or novel CNV associated with familial obesity, have found CNV of FTO relevant, which supports a lack of CNV contribution to genetic risk for obesity (Serra-Juhé et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…We performed a literature search to identify genes related to the melanocortin pathway and the development of the hypothalamus (1,5,12,18,19,21,(26)(27)(28)(29)(30)(31)(32)(33). The 24 genes included in the panel were: (1) genes in which variants have previously been reported to cause or associate with obesity (ADCY3, BDNF, CPE, GRPR, LEP, LEPR, LRP2, MC3R, MC4R, MRAP2, MYT1L, NPY, NTRK2, PCSK1, POMC, SH2B1, SIM1, TUB) and (2) genes previously reported in animal models/linkage analysis/CNV studies to be involved in the melanocortin pathway or development of hypothalamus (ARNT2, ISL1, NEUROG3, OTP, OXT, POU3F2).…”
Section: Genes In the Panelmentioning
confidence: 99%
“…For example, common single nucleotide polymorphisms (SNPs) in multiple genes have been shown to modulate the risk of obesity, although each of these have only a minor effect on body mass index (BMI) variation (2,3). We and others have also shown that rare copy number variants (CNVs) are enriched in patients with early-onset severe obesity (4)(5)(6). Recently, it has also been suggested that obesity could be a consequence of rare genetic variants with strong effect (7,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early-onset obesity (EOO) is one of the most important global health problems resulting in several comorbidities with predisposition to obesity and related diseases during adulthood. 1 EOO is a heritable disorder with a range of genetic factors interacting with environmental exposures. 2 WHO has estimated that the majority of children with obesity live in developing countries, where the rates are increasing faster than in developed countries.…”
Section: Introductionmentioning
confidence: 99%